Indonesia’s Archipelagic Sea Lanes (ASLs) Designation: Rights Turning to Obligations? - Dhiana Puspitawati (Faculty of Law, Hasanuddin University, 2018)
Indonesia is the first and only archipelagic state which has designated Archipelagic Sea Lanes (ASLs). However, such ASLs was only considered as a ‘Partial ASLs’ by the International Maritime Organization (IMO). This is due to the lack of the inclusion of all normal passage routes used for international navigation as required by Article 53 (4) of Law of the Sea Convention (LOSC). On the other hand, Indonesian national law stated that the rights of ASLP can only be exercised over the designated routes and this leave the undesignated routes under the innocent passage regimes, which is inconsistent with Article 53 (12) of LOSC. This article seeks to analyse Indonesia’s rights in designating ASLs and the implementation of Indonesia’s ‘Partial ASLs’. It is questionable whether Indonesia’s rights in designating ASLs has become an obligation by the ‘partial’ recognition of Indonesia’s ASLs by IMO. While none reported incident of navigational rights over Indonesia’s north-south ASLs, however some incidents did occur over the undesignated east/west ASLs. This paper begins with the analyses of the provisions of LOSC concerning archipelagic sea lines passage by looking at its travoux-preparatoir and then follows by the discussion of Indonesia’s implementation on its designated ASLPs. Reported incident occurred over the undesignated ASLs will also be discussed to gain clear understanding on the matter. It is argued that Indonesia should either designated the east/west ASLs or if not, adjusting its national law to be in conformity with LOSC.